PERAN DOSEN PEMBIMBING AKADEMIK ( PA ) TERHADAP PRESTASI BELAJAR MAHASISWA ( Studi Kasus di Program Studi Pendidikan Ekonomi Jurusan P.IPS FKIP) - Susilowati, Tutik (MIIPS, 2008)
This research aims to: 1) know the role of academic supervisor of Educational Economy major to enhance studentâs learning achievement, 2) to find out the time duration the academic supervisors take to do the counseling, 3) to find out the problems in counseling.This research uses descriptive qualitative method and the embedded case study. The data come from informants, the research locations and documents. The research uses the purposive sampling technique. The data collection is done with interviews, observations and document analysis. The data validation uses data triangulation pattern and the resource. The data analysis is conducted with interactive analysis pattern technique.The results of the research conclude that: 1) the academic supervisor functions as the information resources, the one to accommodate, listen the problems of the students, help the students to resolve the problems, give suggestions and monitor the learning activities of his/her students, 2) the counseling is done at: the beginning of the semester, the middle semester and the end of semester, 3) problems to conduct counseling come from both the academic supervisors and the students